Pulmonary Resection for Metastasis of Hepatocellular Carcinoma Recurring After Liver Transplant: An Italian Multicenter Experience - Invenizzi, Federica; Iavarone, Massimo; Donato, Maria Francesca; Mazzucco, Alessandra; Torre, Massimo; Conforti, Serena; Rimessi, Arianna; Zavaglia, Claudio; Schiavon, Marco; Comacchio, Giovanni; Rea, Federico; Boetto, Riccardo; et al. (Frontiers in Oncology, 2020)
Background and aim: Liver transplantation (LT) is an established treatment for hepatocellular carcinoma (HCC). HCC recurrence occurred between 8 to 20% of patients and lung is the most frequent site. Pulmonary metastases resection (PMR) prolongs survival, however in LT-setting the impact on survival is unclear. To shed new lights on this topic, we report the experience of three Italian LT Centers. Methods: All consecutive HCC transplanted patients in three Italian LT Centers, who developed pulmonary metastasis from HCC (PM-HCC), as first metastasis, from 2008 to 2018, were included whenever treated with PMR. Results: Twenty-five patients were enrolled (median age 58 yrs, 84% male, 3% cirrhotics). HCC recurred after 34 months (9-306) since LT and PMR was performed after 2.4 months (0-43.1). A total of 28 PMR (19 single resections; 9 multiple resections; 16 right; 2 left) have been performed on 24 patients while in one case percutaneous microwave ablation (MWA) was preferred. Four patients have been re-operated due to pulmonary HCC-recurrence after surgery. The majority of surgical resection type was wedge resection (26, 89%). Surgical access was: video-assisted thoracic surgery (VATS) in 17 cases (59%); thoracotomy in 11 (38%); MWA in 1 (3%). The 48% of nodule was in right lower lobe. Perioperative in-hospital mortality and 30-day mortality were nil; median surgical time 90 minutes (50-365); median post-operative overall stay 5 days (2-11). Post-operative ICU treatment was necessary in 1 case (3%) for 3 days; blood transfusions in 2 cases (7%). Overall, 5 complications (2 bleeding; 1 AKI; 1 major cardiac; 1 wound dehiscence) occurred, with an overall complications rate of 23%. Eight (32%) patients died during a follow-up after HCC recurrence of 32 months (7-213): 7 for HCC progression, 1 for severe liver failure due to chronic rejection. The 1 and 5-year cumulative probability of OS from recurrence were 100% and 43% (95%CI 12-74), respectively, with a median OS of 51 months (95%CI 24-78). Conclusion: Selected patients with isolated pulmonary HCC-recurrence after LT and with a good hepatic function showed that a pulmonary metastasectomy is effective in controlling a PM-HCC and can offer the only chance for long-term survival